x^2 12-x _____ = _____ X^2-9 X^2-9

x^2 12-x
_____ = _____
X^2-9 X^2-9

  • x^2 12-x

    _____ = _____

    X^2-9 X^2-9

    х^2/x^2-9 + x/x^2-9 — 12/x^2-9

    x+4/x+3=0

    1/x+3=0

    x= -4

  • x^2 12-x

    _____ = _____

    X^2-9 X^2-9

    х+х-12

    _______=0

    х-9

    Решаем числитель

    х+х-12=0

    D=49=7

    х=-4

    х=3

    А знаменатель рескроем по формуле. Получается:

    (х-3)(х+4)

    _________=0

    (х-3)(х+3)

    х-3 сокращаются и остается

    х+4

    ___=0

    х+3

    Так, как х получился -4 и 3, подставем сначала -4

    -4+4

    ____=0

    -4+3

    0

    _=0 (правильно)

    -1

    Теперь подставим 3

    3+4

    ___=0

    3+3

    7

    _0(не подходит)

    6

    Ответ: -4